A new species of Hygrogeus Mulsant & Rey, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from Xizang, China - Cheng, Zhi-Fei; Peng, Zhong (Zootaxa, 2019)
The first species of the genus Hygrogeus Mulsant & Rey (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China is described, under the name of Hygrogeus chinensis sp. n.. The type material has been collected from West Duoxiongla Mountain and Sejila Pass in Xizang, China; the habitus, aedeagus, mouthparts of the new species are illustrated.